A case of left sided gastroschisis with pulmonary hypoplasia - Srivastava, Subhi; A., Sendhil Coumary (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Gastroschisis is a congenital paraumbilical anterior abdominal wall defect resulting in herniation of abdominal wall contents. Incidence of gastroschisis is 5 per 10,000 live births. Usually, it is right sided and left sided gastroschisis is rare. Gastroschisis in itself has a good prognosis, but the prognosis may vary with the severity of associated conditions. This article reports a case of left sided gastroschisis associated with pulmonary hypoplasia.